PENENTUAN PENGGUNAAN LAHAN KOSONG DENGAN ANALISIS HIGHEST AND BEST USE (HBU) - Mulyana, Elfan Wahyu (Program Sarjana Manajemen Universitas Internasional Batam, 2019)
This research aims to determine the land use with the highest and best use analysis on a vacant lot owned by Mr. Johan in Tanjungpinang City. Methodology research used by analysis of productivity of land covering aspects of the physical and legal aspects, as well as a location to obtain use of alternative possibilities. Further analysis is the analysis of the appropriateness of the market, namely supply and demand analysis of the market, as well as financial feasibility analysis for each proposed use. In this study, the data to be analyzed is composed of primary data and secondary data. Primary Data include data on income from the sale of property types and alternative expenditure proposed as an alternative to the use of, obtained by interview, while the physical data including size, shape, topography, site utilities and others obtained through direct investigation. The secondary Data were obtained from the Central Agency of statistics and several organizations in the area of Government of the city of Tanjungpinang. Based on the results of the analysis of productivity obtained three proposals for land use and housing development which allows the top, where housing as an alternative here, is the kind of simple housing, medium and luxury residential housing. Based on market analysis and financial feasibility, provided the value of the Net Present Value (NPV), the use of intermediate housing is an alternative use of the most optimal.